Teaching Concurrency and Parallelism Concepts with CMRE - De Giusti, Laura Cristina (2016)
Possible methodologies for teaching the concepts of processor heterogeneity and its impact on speedup and efficiency in a parallel system are discussed, as well as energy efficiency of parallel algorithms based on processor power. CMRE (Concurrent Multi Robot Environment) is expanded to be able to consider different virtual clocks in each robot (processor), as well as the cost – both in relation to time and energy consumption – of the operations carried out by the robots (Move, Put Down / Pick Up / Message / Inform). In this paper, we analyze some examples to show how concepts are introduced to students.